The Development of the Indonesian Culture Gunungan Design: Wayang Godhong “Smoking Violated” - Purwantoro, Agus; Prameswari, Nadia Sigi; @ Mohd Nasir, Roziani Binti Mat Nashir (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2022)
This study explores the development of innovative wayang craft designs in Magelang, Central Java, Indonesia. This is necessary research because wayang functions as a medium of contextual communication between the puppeteer and an audience by transmitting the values of life through entertainment. However, it is rare to find all-night-long wayang performances currently; there is a considerable probability of this craft going extinct in the next few years. This is a research and development method. The type of research and development uses the ADDIE model. Data collection techniques were carried out through interviews, observations, and documentation of Wayang Godhong. The respondents were tobacco farmers and puppeteers in Magelang City, Central Java Province, Indonesia. The result led to the development of Wayang Godhong design which adopts the structures and shape of tobacco leaves. Despite the use of this leaf, the message “smoking is violated” is boldly written on its body. The researcher also implemented the Wayang Godhong product through a puppet show entitled “Smoking Violated” performed on youth and social activists in Magelang Regency. The message from the show is social criticism to the public of the prohibition on smoking in public places, which is still being violated. The results showed that the public accepted the Wayang Godhong performance and positively impacted public knowledge and awareness regarding the prohibition of smoking in public places.